Customer and employee-based brand equity driving United Bank for Africa's market performance - Uford, Imoh Charles (My University, 2017)
With increased competition in the banking industry, particularly in developing economies, United Bank of Africa Plc (UBA) in Nigeria has been thriving. The bank is a multinational financial services provider, which operates in 22 African countries. It also has offices in the US, UK and France. UBA has about 626 global branches and serves more than seven million retail, commercial and corporate global customers. Positioned as a pan-African bank, the UBA Group is firmly in the forefront of driving the renaissance of the African economy. It is also well positioned as a one-stop financial services institution, with growing reputation as the face of banking on the African continent. UBA Plc has grown over the years from being just a brand name to a house hold name in Nigeria. In 2011, it was reported that UBA’s total assets was worth about $12.3 billion. The bank is also gearing to be one of the dominant and leading banking brands in Africa. While the measurement of UBA’s asset worth is important as it reveals information of its financial performance, it can be more important to measure the worth of its intangible assets, which is being captured from the assessment of its brand equity. Brand equity does not only comprise of an organization’s intangible assets, but does reflect the values consumers hold of a brand and can also secure long-term commercial and competitive advantages for companies. With the notion that the value or power of a brand lies in what customers perceive in their minds concerning the brand, most studies have measured brand equity mainly from the customer-based brand equity (CBBE) perspective using Aaker’s (1996a) and Keller’s (1998) models. Aaker’s (1996a) model is however considered to be the most comprehensive CBBE model and it measures brand equity from five dimensions – brand awareness, brand association, perceived quality, brand loyalty and proprietary assets. While CBBE can secure long-term market performance, it is being recommended that the contribution of employee-based brand equity (EBBE) should also be measured. This is particularly important in the service sector, such as banking, where “what is delivered is less important than how it is delivered”. More so, with the increasing importance of internal branding, there is a need to measure EBBE, which assesses how knowledgeable, happy and committed employees are willing to deliver on the brand promises to build brand equity. In addition to the importance of measuring both CBBE and EBBE, there is also the need to further compare the extent to which both CBBE and EBBE predict market performance, an outcome anticipated, but rarely empirically tested. This study therefore employs Aaker’s (1996) CBBE model and Kwon’s (2013) EBBE model to examine the sources of UBA’s CBBE and EBBE respectively and the extent to which each of the equities drive market performance indicators, such as consumer purchase intention, willingness to pay a price premium and brand preference. A positivist research paradigm with a quantitative survey of 182 UBA employees and 178 UBA customers were used to test the hypotheses. The relationships hypothesized in the conceptual model were empirically tested using structural equation modeling (SEM). The results indicated that the conceptual model satisfactorily fitted the data and provided reasonable explanations among variables. In terms of the relationships, it was found that UBA’s CBBE was accounted for by brand associations or image and brand loyalty. UBA’s overall CBBE positively and significantly affected all the market performance indicators of purchase intention, willingness to pay a price premium and brand preference. UBA’s EBBE which was found to be positively and significantly driven by role clarity and brand commitment could only positively and significantly predict the bank customers’ willingness to pay a price premium. Conclusively, it was found that while UBA’s EBBE make some contribution to the bank’s market performance, its CBBE is the major driver of its performance. This study theoretically contributes by not only empirically testing Aaker’s (1996b) CBBE and Kwon’s (2013) EBBE in the Nigeria’s banking sector, but by also showing how both models explain market performance. Practically, the study reveals sources of CBBE and EBBE, which not only UBA should prioritize in improving their market performance, but other service sectors in Nigeria and the continent should take special note of. Keywords: Brand equity, customer-based brand equity (CBBE), employee-based brand equity (EBBE), United Bank for Africa (UBA) Plc, United Bank for Africa (UBA) Plc, structural equation modelling (SEM), United Bank for Africa (UBA) Plc, willingness to pay a price premium and brand preference
Thesis submitted in full fulfilment of the requirements for the degree of doctor of philosophy (Marketing) at the University of the Witwatersrand, Johannesburg. November 2017.
Keywords: Brand equity; Customer-based Brand Equity (CBBE); Employee-based Brand Equity (EBBE); United Bank for Africa (UBA) Plc; Structural Equation Modelling (SEM); Willingness to pay a price premium and brand preference; Banks and banking--Nigeria; Brand name products; Corporate image